In keeping with the digital age planning and adoption of Information and Communication Technology (ICT) among communication educators in the Philippines - Alagaran, Jose Reuben Q.
" This dissertation focused on how communication educators in the Philippines plan and adopt information and communication technology (ICT) in teaching and learning communication courses. Eighty-three (83) communication teachers, chosen through snowball sampling, participated in the survey. Interviews with Philippine Association of Communication Educators (PACE) President and Commission on Higher Education Technical Panel Chair and documents review of CHED Policies and Standards on Communication Programs complemented the survey. In general, the respodents use ICT for communication, research and presentation purposed and not so much for content creation and development, such as multimedia authoring, digital audio/video streaming, and podcasting. They plan their communication curriculum content based on expected competencies of graduates, which the key informants and CHED Policies also encourage. They also develop the curriculum to match the available ICT equipment in their schools and the ICT competencies of teachers. In keeping with the digital age, the educators would attend professional development programs and help institutionalize ICT integration through the development of ICT policies. In so doing, they are still able to respond to the requirements of the digital age in their own little but varied ways. "